2016
DOI: 10.1038/srep32338
|View full text |Cite
|
Sign up to set email alerts
|

Prions efficiently cross the intestinal barrier after oral administration: Study of the bioavailability, and cellular and tissue distribution in vivo

Abstract: Natural forms of prion diseases frequently originate by oral (p.o.) infection. However, quantitative information on the gastro-intestinal (GI) absorption of prions (i.e. the bioavailability and subsequent biodistribution) is mostly unknown. The main goal of this study was to evaluate the fate of prions after oral administration, using highly purified radiolabeled PrPSc. The results showed a bi-phasic reduction of PrPSc with time in the GI, except for the ileum and colon which showed sustained increases peaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Using extremely sensitive PrP Sc -based detection assays, two independent studies reported the presence of low/trace levels of prions in the blood-stream within minutes of oral exposure [81, 82]. The cellular route through which the prions initially gained access to the blood-stream was not determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using extremely sensitive PrP Sc -based detection assays, two independent studies reported the presence of low/trace levels of prions in the blood-stream within minutes of oral exposure [81, 82]. The cellular route through which the prions initially gained access to the blood-stream was not determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with radioactively labeled scrapie prions in mice demonstrated prions can rapidly cross the intestinal mucosa in minutes, followed by distribution to systemic organs via the vascular system (38). Investigations of specific routes of intestinal uptake of transmissible mink encephalopathy and scrapie prion have identified M cells of the follicle-associated epithelium of Peyer's patches as a site of prion entry (39,40).…”
Section: Figmentioning
confidence: 99%
“…For these studies, we radiolabeled the protein with 125 -Iodine, a method that we have extensively used in previous studies and shown not to alter the biological and biochemical properties of PrP Sc (28)(29)(30)(31) (32,33). To assess the ability of surface-bound prions to self-propagate, beads were incubated with serially diluted 263K prion-infected brain homogenate, extensively washed and air-dried; then, used to seed PMCA as previously described (32).…”
Section: Binding and Release Of Prions From Environmental Surfacesmentioning
confidence: 99%
“…Sc was purified using detergent extraction and PK digestion, as previously described (31). Briefly, 10% (w/v) brain homogenate was prepared in PBS supplemented with proteinase inhibitor (complete, Roche) and 10% sarkosyl (final concentration).…”
Section: Prpmentioning
confidence: 99%
See 1 more Smart Citation